The Role of Semaphorins and Their Receptors in Innate Immune Responses and Clinical Diseases of Acute Inflammation - Kanth, Shreya M.; Gairhe, Salina; Torabi-Parizi, Parizad (Frontiers in Immunology, 2021)
Semaphorins are a group of proteins that have been studied extensively for their critical function in neuronal development. They have been shown to regulate airway development, tumorigenesis, autoimmune diseases, and the adaptive immune response. Notably, emerging literature describes the role of immunoregulatory semaphorins and their receptors, plexins and neuropilins, as modulators of innate immunity and diseases defined by acute injury to the kidneys, abdomen, heart and lungs. In this review we discuss the pathogenic functions of semaphorins in clinical conditions of acute inflammation, including sepsis and acute lung injury, with a focus on regulation of the innate immune response as well as potential future therapeutic targeting.